PENAMBAHAN FLY ASH DAN SERAT SERABUT KELAPA SEBAGAI BAHAN PEMBUATAN BETON - Eko Siswanto; April Gunarto (U Karst, 2019)
Along with the development of technology today many types of materials and mixtures are used. This study used concrete K-225 jobmix and carried out the addition of coconut fiber as an addition to coarse aggregate and Fly ash as a cement enhancer.Jobmix variations of concrete are 0%, 10%, 20%, 30%, and 40%. The number of test specimens from each variation was made 3 pieces of specimens in the form of cubes 15 x 15 x 15 cm, testing the specimens was carried out at the age of 28 days. By testing compressive strength and absorption.The results showed that the average compressive strength of concrete in each variation was 0% (2800 kg / cm2), 10% (2520 kg / cm2), 20% (2016 kg / cm2), 30% (1411 kg / cm2) and 40% (846 kg / cm2). From the average - compressive strength of concrete in each variation data obtained that the value of compressive strength of concrete with a variation of 10% is equal to the average value of compressive strength K-225. The optimum percentage of coconut fiber fibers in the compressive strength of concrete at a variation of 10% with the conversion results of 260 kg / cm3 reaching k-225 quality. Absorption test with the addition of coconut fiber fibers and Fly ash in each variation with an average of ¼ hour (0.101 ml), 1 hour (0.046 ml), 4 hours (0.016 ml), and 24 hours (0.037 ml) Keywords: Compressive Strength, Absorption, Coconut Fiber, Fly ash.Seiring dengan perkembangan teknologi saat ini banyak jenis bahan dan campuran digunakan. Penelitian ini menggunakan beton K-225 jobmix dan melakukan penambahan serat kelapa sebagai tambahan agregat kasar dan Fly ash sebagai penambah semen. Variasi beton Jmmix adalah 0%, 10%, 20%, 30%, dan 40% . Jumlah spesimen uji dari masing-masing variasi dibuat 3 buah spesimen dalam bentuk kubus 15 x 15 x 15 cm, pengujian spesimen dilakukan pada umur 28 hari. Dengan menguji kuat tekan dan absorpsi. Hasil penelitian menunjukkan bahwa kuat tekan rata-rata beton pada setiap variasi adalah 0% (2800 kg / cm2), 10% (2520 kg / cm2), 20% (2016 kg / cm2), 30% (1411 kg / cm2) dan 40% (846 kg / cm2). Dari rata - rata kuat tekan beton pada setiap variasi data diperoleh bahwa nilai kuat tekan beton dengan variasi 10% sama dengan nilai rata - rata kuat tekan K-225. Persentase optimal serat serabut kelapa dalam kekuatan tekan beton pada variasi 10% dengan hasil konversi 260 kg / cm3 mencapai kualitas k-225. Uji absorpsi dengan penambahan serat serabut kelapa dan abu terbang di setiap variasi dengan rata-rata ¼ jam (0,101 ml), 1 jam (0,046 ml), 4 jam (0,016 ml), dan 24 jam (0,037 ml)Kata Kunci: Kekuatan Tekan, Penyerapan, Serat Kelapa, Fly ash